Analysis of the Utilization of E-commerce and Social Media on Marketing System of Micro, Small and Medium Enterprises - Setiawan, Ananda; Nabela, Aqlin Neswan; Juliantri, Paulina (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economy in Indonesia. Nowadays, customers are starting to use social media to find various information about a particular brand before making a purchase. Therefore, it is good to consider marketing strategies through e-commerce and social media. This study examines the effect of using E-Commerce and social media in the marketing system of MSMEs among teenagers to increase sales. Data was collected from 252 teenagers in Indonesia through questionnaire distribution and hypotheses were estimated using PLS-SEM with Smart-PLS 4.0. The findings show that MSME players have begun to utilize e-commerce and social media to market their products, some MSME players have mastered various types of features in social media and one of the factors that determine how social media and e-commerce work can be managed properly which has implications for the possibility of increasing sales, proper management to influence the potential for increased sales, good management of social media and e-commerce is also recognized by MSMEs as beneficial in increasing sales among teenagers